Priročnik za obvladovanje psihosocialnih tveganj in absentizma s pomočjo orodja e-OPSA Prilagojena različica za dejavnosti zdravstvenega in socialnega sektorja - Cukut Krilić, Sanja (ZRC SAZU, Založba ZRC, 2016)
A handbook for managing psychosocial risks and absenteeism with e-OPSA tool' is an integral part of the new, freely available tool aimed at management of psychosocial risks and health-related absenteeism (e-OPSA~www.opsa.si). An adapted version of e-OPSA for employed in the health and social sector (hospitals, health care centres, homes for elderly people, centres for social work, residential care institutions, etc.). Besides introducing the problem of psychosocial burdens experienced by employees at their workplace and beyond, this handbook can be used as a useful instrument for designing a various promotional and preventive arrangements which bettering employees' health and well-being in their working settings, as suggested by recent guidelines for psychosocial risks management. A handbook is based on interactive chapters, including also numerous links to supportive health promotion websites in order to facilitate the preparation of adequate measures and related activities, commonly carried out by professionals in the field of health and safety at work. A special chapter is dedicated to instructions for working with an online tool e-OPSA tool, enabling an assessment of employees' psychosocial burdens and risks of developing an excessive stress, absenteeism, presenteeism, turnover and experiencing of workplace violence.